Nigel Dodd (1965-2022) obituary - Patrik Aspers (economic sociology. perspectives and conversations, 2022)
Nigel Dodd passed away in London on August 12, 2022, after a period of illness. Dodd was professor of sociology at the London School of Economics and Political Science, which he joined in 1995. He earned his doctorate in 1991 at the University of Cambridge, with Anthony Giddens as his supervisor. His dissertation was published in 1994 by Polity Press with the title The Sociology of Money, Economics, Reason and Contemporary Society. Dodd was the editor of Volume 12 of this publication (2010-2011).
Keywords: 300